Corporate Governance, Ethics, and the Backdating of Stock Options - Adam, Avshalom M. (Journal of business ethics, 2009)
Backdating of stock options is an example of an agency problem. It has emerged despite all the measures (i.e., new regulations and additional corporate governance mechanisms) aimed at addressing such problems? Beyond such negative controlling measures, a more positive empowering approach based on ethics may also be necessary. What ethical measures need to be taken to address the agency problem? What values and norms should guide the board of directors in protecting the shareholders’ interests? To examine these issues, we first discuss the role values and norms can play with respect to underlying corporate governance and the proper role of directors, such as transparency, accountability, integrity (which is reflected in proper mechanisms of checks and balances), and public responsibility. Second, we discuss various stakeholder approaches (e.g., government, directors, managers, and shareholders) by which conflicts of interest (i.e., the agency problem) can be addressed. Third, we assess the practice of backdating stock options, as an illustration of the agency problem, in terms of whether the practice is legally acceptable or ethically justifiable. Fourth, we proceed to an analysis of good corporate governance practice involving backdating options based on a series of ethical standards including: (1) trustworthiness; (2) utilitarianism; (3) justice; and (4) Kantianism. We conclude that while executive compensation schemes (e.g., stock options) were originally intended to help remedy the agency problem by tying together the interests of the executives and shareholders, these schemes may have actually become “part of the problem,” and that the solution ultimately depends upon whether directors and executives accept that all of their actions must be based on a set of core ethical values.